Perjanjian Pinjaman Online Berbasis Financial Technology (Fintech) - Ni Made Eka Pradnyawati; I Nyoman Sukandia; Desak Gde Dwi Arini (Warmadewa Press, 2021)
Financial Technology (Fintech) is a technology alternative that facilitates loan transactions that can be done online. Online loans create new problems such as rampant fraud and default. Referring to the problems described, this research was conducted with the aim of explaining the legal position of financial technology-based online loan agreements (Fintechl), and knowing the legal protection of creditors who provide financial technology-based online loans (Fintech). This research used normative legal research. Sources of data are primary and secondary legal materials, data are combined with recording techniques in obtaining primary and secondary legal materials, namely examining several reading materials such as journals, scientific books and statutory regulations. After the data is collected, it is then analyzed qualitatively. The result showed that the legal position of online loan agreements based on financial technology (Fintech) when reviewed legally, the online agreement is legally valid because it has a basis, namely Article 1320 of the Civil Code and the validity of the evidence used refers to law Number 11 of 2008 concerning Article 5 of the ITE Law on information, documents and electronic signatures. Legal protection for creditors in an online loan agreement based on financial technology (Fintech) consists of preventive legal protection and repressive legal protection.